Novel Regrowth-Free Vertical Active-Passive Integration Scheme with Improved Fabrication Tolerance - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2005)
We present a novel vertically-coupled active-passive integration architecture that provides an order of magnitude reduction in coupling coefficient variation between misaligned waveguides when compared with a conventional vertically-coupled structure.